An Analysis of EdTech Learners : The Influence of Brand Experiences on Word-of-Mouth and Brand Loyalty - Riyat, Manpreet Kaur; Kakkar, Amit (Prabandhan: Indian Journal of Management, 2025)
Purpose : The present study investigated the relationship between brand experiences, hedonic values, utilitarian values, user engagement, continuous intention, and word of mouth (WOM) in the educational technology (EdTech) sector. It aimed to understand how brand experience influenced customer value and engagement, ultimately driving brand loyalty and positive WOM. Methodology : The study was conducted among working professionals from Northern India, including teachers, researchers, IT professionals, managers, and consultants focused on skill development. Using convenience and snowball sampling, 1,162 valid responses were collected, ensuring participants had prior experience and completed at least one course on an Edtech platform. Data analysis was performed using Smart PLS software. Findings : The results indicated that the dimensions of affective, behavioral, and intellectual brand experience enhanced hedonic and utilitarian values. A strong correlation was found between customer value and engagement. The study also corroborated the positive influence of engaged customers on continuous intention to use EdTech platforms and share positive WOM. Practical Implications : This study provided EdTech firms insights into enhancing customer retention and advocacy strategies. Strengthening brand experiences, enhancing customer value, and driving engagement can lead to greater brand loyalty and positive WOM, contributing to competitive advantage in the industry. Originality : By expanding existing research on brand experience in the EdTech sector, this study offered practical recommendations for improving user engagement and retention. It contributed to a deeper understanding of how brand experiences shaped customer perceptions and behaviors, providing valuable implications for EdTech platforms.